Antifungal activity and physical characterization of an experimental dentifrice containing carvacrol - Maria Thais Macedo; Ellen Silva Oliveira; Jocianelle Nunes; Fábio Sampaio; Isabela Albuquerque Passos Farias (Editorial Ciencias Médicas, 2023)
Introduction: The successful treatment of oral candidiasis depends on three essential principles, namely: early and accurate diagnosis, correlation with predisposing factors or underlying diseases that compromise immunity, and appropriate use of antifungal drugs. Objectives: To determine the minimum inhibitory concentration of carvacrol against Candida albicans and to develop and evaluate the in vitro antifungal activity (diameter of inhibition zone) and physical properties (foaming capacity, spreadability and cleaning capacity) of an experimental dentifrice containing carvacrol. Methods: The carvacrol was incorporated into a dentifrice base at different concentrations and tested for its minimum inhibitory concentration and agar diffusion against Candida albicans and the physical properties. Data were analysed by ANOVA. Results: The minimum inhibitory concentration of carvacrol was 1041.67 ± 360.84 µg/mL. The dentifrice containing carvacrol C1 e C2 produced an inhibition zone of 27.50 ± 2.12 mm and 36.66 ± 2.08 mm, respectively (p<0.05). As for the physical properties, the dentifrices showed no foaming capacity, while their cleaning capacity and spreadability remained unaltered. Conclusions: The experimental dentifrices containing carvacrol showed antifungal activity. The incorporation of carvacrol significantly altered the foaming capacity of the formulations, without any significant effects on their cleaning capacity and spreadability.